Design, Synthesis, and Antibacterial Evaluation of Novel Ocotillol Derivatives and Their Synergistic Effects with Conventional Antibiotics - Doudou Zhang; Yucheng Cao; Kaiyi Wang; Zhuoyue Shi; Ruodong Wang; Qingguo Meng; Yi Bi (Molecules, 2021)
The improper use of antibiotics has led to the development of bacterial resistance, resulting in fewer antibiotics for many bacterial infections. Especially, the drug resistance of hospital-acquired methicillin-resistant Staphylococcus aureus (HA-MRSA) is distinctly serious. This research designed and synthesized two series of 3-substituted ocotillol derivatives in order to improve their anti-HA-MRSA potency and synergistic antibacterial activity. Among the synthesized compounds, 20–31 showed minimum inhibitory concentration (MIC) values of 1–64 µg/mL in vitro against HA-MRSA 18–19, 18–20, and S. aureus ATCC29213. Compound 21 showed the best antibacterial activity, with an MIC of 1 μg/mL and had synergistic inhibitory effects. The fractional inhibitory concentration index (FICI) value was 0.375, when combined with chloramphenicol (CHL) or kanamycin (KAN). The structure–activity relationships (SARs) of ocotillol-type derivatives were also summarized. Compound 21 has the potential to be developed as a novel antibacterial agent or potentiator against HA-MRSA.